Spatial mRNA Expression and Response to Fasting and Refeeding of Neutral Amino Acid Transporters slc6a18 and slc6a19a in the Intestinal Epithelium of Mozambique tilapia - Orozco, Zenith Gaye A.; Soma, Satoshi; Kaneko, Toyoji; Watanabe, Soichi (Frontiers in Physiology, 2018)
The mRNA expressions of the epithelial neutral amino acid transporters slc6a18 and slc6a19a in the five segments (HL, PMC, GL, DMC and TS) of the intestine of Mozambique tilapia, and their responses to fasting and refeeding were investigated for a better understanding of the functional and nutritional characteristics of slc6a18 and slc6a19a. Although both slc6a18 and slc6a19a were expressed mainly in the intestine, these genes showed opposing spatial distributions along the intestine. The slc6a18 was mainly expressed in the middle (GL) and posterior (DMC and TS) intestines, while slc6a19a was specifically expressed in the anterior intestine (HL and PMC). Large decreases of amino acid concentrations from the HL to GL imply that amino acids are mainly absorbed before reaching the GL, suggesting an important role of slc6a19a in the absorption. Moreover, substantial amounts of some neutral amino acids with the isoelectric point close to 6 remain in the GL. These are most likely the remaining unabsorbed amino acids or those from of amino acid antiporters which release neutral amino acids in exchange for uptake of its substrates. These amino acids were diminished in the TS, suggesting active absorption in the posterior intestine. This suggests that slc6a18 is essential to complete the absorption of neutral amino acids. At fasting, significant downregulation of slc6a19a expression was observed from the initial up to day 2 and became stable from day 4 to day 14 in the HL and PMC suggesting that slc6a19a expression reflects nutritional condition in the intestinal lumen. Refeeding stimulates slc6a19a expression, although expressions did not exceed the initial level within 3 days after refeeding. The slc6a18 expression was decreased during fasting in the GL but no significant change was observed in the DMC. Only a transient decrease was observed at day 2 in the TS. Refeeding did not stimulate slc6a18 expression. Results in this study suggest that Slc6a18 and Slc6a19 have different roles in the intestine, and that both of these contribute to establish the efficient neutral amino acid absorption system in the tilapia.